Development of Story Teaching Materials to Increase Children's Reading Interest in Social Education Sciences at Junior high school of Klaten Regency - Iswan Riyadi (Edumaspul: Jurnal Pendidikan, 2021)
This research aims to develop storytelling teaching materials to increase children's reading interest in social studies subjects at SMP Kab. Klaten. The method used in this research is Research and Development (R&D). The preliminary study stage is the stage that is carried out for the first time in R&D research, and the initial study consists of three stages, namely: literature study, field survey, and preparation of product drafts. The second stage is the product development stage. The researcher sends the product developed to the validator to be validated by experts according to their field. The results of this study are that storytelling teaching materials are feasible to use and very effective in increasing students' interest in reading, which can be proven by the feasibility of this product as evidenced by the results of validation carried out by several teachers, namely material expert teachers, two media experts, three linguists, and story experts. Validation results with successive percentage results, namely 95%, 85%, 80%, and 79%.